2008
DOI: 10.1679/aohc.71.163
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of apoptosis by glycyrrhizin in hepatic injury induced by injection of lipopolysaccharide / D-galactosamine in mice

Abstract: Summary. The inhibition of apoptosis by glycyrrhizin (GL) in hepatic injury induced by injection of lipopolysaccharide (LPS)/D-galactosamine (D-GalN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…The injection of LPS/GalN signiicantly increases serum AST and ALT activities as compared with controls. The enhancement of AST and ALT levels is signiicantly suppressed by an intraperitoneal administration of GL (Figure 1; [19,37,38]). Administration of LPS/GalN precipitate tissue injury associated with time-dependent alteration in HMGB1 serum levels.…”
Section: Resultsmentioning
confidence: 96%
“…The injection of LPS/GalN signiicantly increases serum AST and ALT activities as compared with controls. The enhancement of AST and ALT levels is signiicantly suppressed by an intraperitoneal administration of GL (Figure 1; [19,37,38]). Administration of LPS/GalN precipitate tissue injury associated with time-dependent alteration in HMGB1 serum levels.…”
Section: Resultsmentioning
confidence: 96%
“…28, 29 It has been suggested that glycyrrhizin possibly acts as a radical scavenger in the cytoplasm of hepatocytes and decreases cell membrane permeability. 17 A previous report has shown that intravenous glycyrrhizin can effectively protect liver against fulminant hepatic failure induced by lipopolysaccharide/ d -galactosamine in mice, and that glycyrrhizin prevents hepatocytes' apoptosis by inhibiting inflammatory reaction and stabilizing mitochondria membrane to suppress the release of cytochrome C and sequential activation of caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported that pre-treatment of intravenous glycyrrhizin (Stronger Neo-Minophagen C, SNMC) can effectively protect liver against fulminant hepatic failure induced by lipopolysaccharide (LPS)/D-galactosamine (D-Gal N) in mice, and that SNMC prevents hepatocyte apoptosis by inhibiting inflammatory reaction and stabilizing mitochondria membrane to suppress the release of cytochrome C and sequential activation of caspase-3 [22]. Ikeda et al reported that glycyrrhizin inhibited the apoptosis of liver cells through the prevention of an IL-18-mediated inflammatory response in a caspase-independent manner in LPS/D-GalNinduced mouse liver injury [23].…”
Section: Discussionmentioning
confidence: 99%